2009
DOI: 10.1590/s1516-635x2009000200006
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alternative forced-molting methods on the performance and egg quality of commercial layers

Abstract: This study aimed at studying alternative methods to induce molting and to compare them with the conventional forced-molting method (fasting). In the experiment, 420 70-week-old layers were used. The total experimental period was 140 days. Molting was induced during the first 28 days, when birds were submitted to the experimental treatments, and bird performance and egg quality parameters were determined during 112 subsequent days. A completely randomized experimental design was applied in a 5x2 factorial arran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…The results of eggs' production in the postmolting phase are in agreement with previous studies (RAMOS et al, 1999;KESHAVARZ;QUiMBY, 2002;MOLiNO et al, 2009). in these publications, the number of eggs was greater for birds that received total feed restriction for inducing molt.…”
Section: Resultssupporting
confidence: 92%
“…The results of eggs' production in the postmolting phase are in agreement with previous studies (RAMOS et al, 1999;KESHAVARZ;QUiMBY, 2002;MOLiNO et al, 2009). in these publications, the number of eggs was greater for birds that received total feed restriction for inducing molt.…”
Section: Resultssupporting
confidence: 92%
“…Park et al (2004) reported body weight loss of 15.52 and 15.60 % over 9 days in laying hens moulted with zinc acetate and zinc propionate, respectively while those subjected to feed withdrawal lost 25.12 % of their body weight within the same period. Molino et al (2009) observed body weight loss of 21.19 % by D 7 in hens undergoing fasting moult which agreed with the result of the present study. Whatever the moulting method employed, body weight loss of 25 to 30 % has been advocated to optimize post moult performance (Sohail et al, 2011).…”
Section: Trend In Performance Of Hens During the Moulting Phasesupporting
confidence: 93%
“…Induced moulting rejuvenates the hen's reproductive organs and improves the post-moult performance of the flock in livability, egg production, and egg quality compared to the immediate pre-moult performance (Holt, 2003;Webster, 2003). Programmes used to induce moulting in laying hens include feed deprivation, photoperiod reduction, mineral (Ca, Cu, Zn, Al, etc) supplementation and the use of low energy diets (Molino et. al., 2009;Santos et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The practice of forced molting to extend the longevity of laying hens has been widely studied and several methods have showed effective results in term of egg quality and quantity (Berry, 2003;Molino et al, 2009;Aygun, 2013). However, there a few studies with quails.…”
Section: Introductionmentioning
confidence: 99%